Do Alternative Base Periods Increase Unemployment Insurance Receipt Among Low‐Educated Unemployed Workers?. (19th July 2013) - Gould‐Werth, Alix; Shaefer, H. Luke
Abstract: Unemployment Insurance (UI) is the major social insurance program that protects against lost earnings resulting from involuntary unemployment. Existing literature finds that low‐earning unemployed workers experience difficulty accessing UI benefits. The most prominent policy reform designed to increase rates of monetary eligibility, and thus UI receipt, among these unemployed workers is the Alternative Base Period (ABP). In 2009, the American Recovery and Reinvestment Act sought to increase use of the ABP, making ABP adoption a necessary precondition for states to receive their share of the $7 billion targeted at UI programs. By January 2013, 40 states and the District of Columbia had adopted the ABP despite the absence of an evaluation of ABP efficacy using nationally representative data. This study analyzes Current Population Survey data from 1987 to 2011 to assess the efficacy of the ABP in increasing UI receipt among low‐educated unemployed workers. We used a natural‐experiment design to capture the combined behavioral and mechanical effects of the policy change. We found no association between state‐level ABP adoption and individual UI receipt for all unemployed workers. However, among part‐time unemployed workers with less than a high school degree, adoption of the ABP was associated with a 2.8 percentage point increase in the probability of UI receipt.